0119 Effect Of Sleep On The Brain-Heart-Gut Axis In A Mouse Model Of TBI And PTSD. (27th April 2018) - Elliott, J E; Teutsch, P; Jones, C E; Li, R; Yang, J; Nguyen, K; Jacobs, J; Li, Z; Hsiai, T; Lim, M M
Abstract: Introduction: Sleep disturbances are common in traumatic brain injury (TBI) and post-traumatic stress disorder (PTSD). While inherently brain disorders, TBI and PTSD are associated with increased risk of cardiovascular and gastrointestinal diseases. Sleep disturbances may also impair cardiovascular and gastrointestinal function. The purpose of this study is to systematically examine the effects of TBI, PTSD, and TBI+PTSD on cardiovascular markers and gut microbiota after a sleep opportunity compared to a period of enforced wakefulness in mice. Methods: Mice were randomized to one of four conditions: Naïve, TBI (controlled-cortical impact), PTSD (Single Prolonged Stress), or TBI+PTSD. Mice (n=10/group, 8 groups) were sacrificed after either a sleep opportunity or period of enforced wakefulness. Brains, serum, terminal ileum, and cecal contents were extracted. Serum was assayed for cardiovascular markers of atherosclerosis and inflammation, while cecum content was assayed for short chain fatty acids (SCFA) and microbiota. Results: TBI and PTSD mice showed elevated cytokine levels of IL1-beta and TNF-alpha during wake, but not sleep. Mice in the TBI and TBI+PTSD groups showed decreased adiponectin levels during wake, but not sleep. There were no group differences in leptin, IL-6, MCP-1, IL-10, IL-8, IL-17, IL-22, or SAA1 and SAA2. Mice in the PTSD and TBI+PTSD groups showed higher SCFA, largely driven by increases in acetic acid. Mice in the TBI, PTSD, and TBI+PTSD groups showed less bifidobacteria species, and using predictive functional profiling, they also showed a decreased ability to degrade the organic insecticide DTT. Finally, several correlations were found between the levels of serum cytokines and the bacterial taxa in cecum. Conclusion: TBI and PTSD increase pro-inflammatory/pro-atherosclerotic cytokines and decrease anti-inflammatory adiponectin, and cause composition alteration and functional impairment in gut microbiota, primarily when the animal is awake. These group differences were not apparent during the sleep condition, suggesting that sleep may help mitigate the deleterious effects of TBI and PTSD on the cardiovascular and gastrointestinal axes. Support (If Any): VA Career Development Award #IK2 BX002712, Medical Research Foundation of Oregon, and the Portland VA Research Foundation to MML.